1985
DOI: 10.1177/153944928500500403
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Occupational Therapists' Education and Experience to Perceived Value of Theory Development

Abstract: The development and validation of theoretical basesfor interuention have been identified as crucial goals for the profession ofoccupational therapy. An earlier study showed that recent graduates at the baccalaureate level tended to place less value on theory development than theory application, whereas graduates of professional master's degree or certificate programs in occupational therapy placed a significantly higher value on theory development. Thisfinding led to speculation that theory valuing may be rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Van Deusen ( 1985) subsequently proposed that theory valuing is related to developmental variables such as years of practice, rather than to academic qualifications alone, but that the two variables had been confounded in her earlier work. To test this hypothesis, she added a sample of 136 experienced therapists to the survey, and compared across both experience and qualifications.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Van Deusen ( 1985) subsequently proposed that theory valuing is related to developmental variables such as years of practice, rather than to academic qualifications alone, but that the two variables had been confounded in her earlier work. To test this hypothesis, she added a sample of 136 experienced therapists to the survey, and compared across both experience and qualifications.…”
Section: Introductionmentioning
confidence: 97%
“…A number of authors in recent years have examined the extent to which occupational therapists value theory (Van Deusen Fox, 1981;Van Deusen, 1985, 1986. In a series of papers published during the past seven years, Van Deusen (1981, 1986 has studied therapists at a variety of points in their careers, with respect to a number of parameters of theory.…”
Section: Introductionmentioning
confidence: 99%
“…Her findings are consistent with those of Fleming and Piedmont (1989) and those of the present study in that therapists in all surveys were concerned about the lack of recognition of the value of occupational therapy services by third-party payers. Van Deusen's (1985, 1986 studies showed that theory development is related to level of education and length of professional experience. Davidson (1981) suggested that theory valuing had a developmental sequence, beginning with valuing theory application, then research and finally theory building.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings and recommendations fall into different areas relevant to this discussion. These are value of theory developments (Van Deusen, 1981;Barris and Kielhofner, 1985;), clinical reasoning skills (Strong et al, 1995), factors contributing to leadership (Scott, 1985;Burke and DePoy, 1991;Schemm and Bross, 1995), factors influencing the development of master clinicians (DePoy, 1990), knowledge of theories (Javetz and Katz, 1989;Munoz et al, 1993), factors leading therapists to cease practice (Rugg, 1996) or to become administrators or clinicians (Bailey, 1988), whether attitudes towards theory developments are related to educational level (Van Deusen, 1985, 1986, perceptions about occupational therapy education (Fleming and Piedmont, 1989), the move from diploma to degree level (Gape and Hewin, 1995), involvement in research activities (Taylor and Mitchell, 1990), the role of occupational therapy and the practitioner (Adamson et al, 1994;Schwartz, 1995a, 1995b;Clark et al, 1995;Brotherton, 1995a, 1995b;Engquist et al, 1997;Moll and Cook, 1997;Vogel, 1991), professional productivity Mann, 1980a, 1980b;Gilkeson and Hanten, 1984;Clark et al, 1985;Storm, 1990), efficacy of one method for teaching reasoning skills (Neistadt, 1992;Neistadt and Smith, 1997), speciality choice in occupational therapy (Ezersky et al, 1989), and experiences occupational therapists have in their practice (Finlay, 1997) …”
Section: Introductionmentioning
confidence: 99%
“…A study designed to test Davidson's conjecture on developmental sequence (Van Deusen, 1985) showed that priority among registered therapists for theory building did increase significantly with increases in amounts of education and experience. Conversely, priority for theory application declined as amounts of education and experience decreased.…”
mentioning
confidence: 98%